DEVELOPMENT OF THE INNOVATIVE TECHNOLOGIES TRANSFER CONCEPTUAL MODEL - Milskaya, Elena; Mednikov, Mihael; Loginova, Nadezhda (Journal of Applied Engineering Science, 2016)
Development of innovative economy in Russia is analyzed in the article, the direction of the effective dissemination of innovation is considered here. We present the concept of innovation active enterprises, the definition of its development potential. The techniques of the transfer of innovative technologies, its conceptual model and, as an option, transfer pricing using probabilistic and expertise.